2009
DOI: 10.1111/j.1476-5829.2008.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Canine cutaneous epitheliotropic T‐cell lymphoma: a review

Abstract: Cutaneous epitheliotropic T-cell lymphoma in the dog is a rare neoplastic condition with unknown aetiology. The dermatitis is characterized by infi ltration of neoplastic T lymphocytes with a specifi c tropism for the epidermis and the adnexal structures. The different clinical and histological forms (mycosis fungoides, pagetoid reticulosis and Sézary syndrome) are reviewed. The disease in the dog resembles the human syndrome, but in 80% of the canine cases, neoplastic cells are CD4− in 90% of the human patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
169
1
31

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(208 citation statements)
references
References 49 publications
7
169
1
31
Order By: Relevance
“…As a comparison, other reports suggested that cutaneous lymphoma (epitheliotrophic and nonepitheliotrophic forms) was detected in only 1% of all canine skin tumors (Goldschmidt and Shofer, 1992;Fontaine et al, 2009). We have diagnosed both epitheliotrophic skin lymphomas (57.15%), as well as non-epitheliotrophic lymphomas (42.85%).…”
Section: Resultsmentioning
confidence: 66%
“…As a comparison, other reports suggested that cutaneous lymphoma (epitheliotrophic and nonepitheliotrophic forms) was detected in only 1% of all canine skin tumors (Goldschmidt and Shofer, 1992;Fontaine et al, 2009). We have diagnosed both epitheliotrophic skin lymphomas (57.15%), as well as non-epitheliotrophic lymphomas (42.85%).…”
Section: Resultsmentioning
confidence: 66%
“…Os linfomas cutâneos têm sido descritos em cães há pelo menos quatro décadas (SHADDUCK et al, 1978;PATTERSON, 1981;NAYDANT, 1994;FOSTER et al, 1997;GROSS et al, 2005;FONTAINE et al, 2009;MOORE et al, 2009;HEIMANN;DAY, 2010;MILLER;GRIFFIN;CAMPBELL, 2013) (ARAÚJO et al, 2012;DIAS et al, 2015;HERNANDEZ, 2017 GROSS et al, 2005;FONTAINE et al, 2009;MOORE et al, 2009;HEIMANN;DAY, 2010;MILLER;GRIFFIN;CAMPBELL, 2013). Não há predisposição sexual e a média de idade dos animais acometidos pela doença é de 9 anos (MOORE; GROSS et al, 2005;FONTAINE et al, 2009;MOORE et al, 2009;HEIMANN;DAY, 2010;MILLER;GRIFFIN;CAMPBELL, 2013;DIAS et al, 2015).…”
Section: Linfoma Cutâneo Caninounclassified
“…Não há predisposição sexual e a média de idade dos animais acometidos pela doença é de 9 anos (MOORE; GROSS et al, 2005;FONTAINE et al, 2009;MOORE et al, 2009;HEIMANN;DAY, 2010;MILLER;GRIFFIN;CAMPBELL, 2013;DIAS et al, 2015). Entretanto, essa correlação é ainda controversa para alguns autores (GROSS et al, 2005;FONTAINE et al, 2009;MILLER;GRIFFIN;CAMPBELL, 2013).…”
Section: Linfoma Cutâneo Caninounclassified
See 2 more Smart Citations